Effect of Ni2+ on Lithium-Ion Diffusion in Layered LiNi1−x−yMnxCoyO2 Materials - Yuanyuan Zhu (Crystals, 2021)
<semantics>LiNi1−x−yMnxCoyO2</semantics> materials are a typical class of layered cathode materials with excellent electrochemical performance in lithium-ion batteries. Molecular dynamics simulations are performed for <semantics>LiNi1−x−yMnxCoyO2</semantics> materials with different transition metal ratios. The Li/Ni exchange ratio, ratio of anti-site <semantics>Ni2+</semantics> to total <semantics>Ni2+</semantics>, and diffusion coefficient of Li ions in these materials are calculated. The results show that the Li-ion diffusion coefficient strongly depends on the ratio of anti-site <semantics>Ni2+</semantics> to total <semantics>Ni2+</semantics> because their variation tendencies are similar. In addition, the local coordination structure of the Li/Ni anti-site is analyzed.